(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article studies the problem of obstacles and misunderstandings, commonly referred as barriers in intercultural communication. The author explores the concepts of "intercultural communication", "cultural barriers» within the framework of culture and communication. Several key barriers such as anxiety, ethnocentrism, stereotypes, prejudices and language barriers were identified, as well as ways of overcoming them were investigated.